أليات إخطار المجلس الدستوري - شافية صياد; زينب بكوش (My University, 2020)
Summary : The notification mechanism constitutes the engine for monitoring the constitutionality of legal texts, even if the latter differs according to the authority issuing them, or in other words, according to the notifying authority. Although the Algerian constitutional founder adopted a dual notification system by approving optional oversight of the constitutionality of laws, where is the notification for the bodies authorized to notify, whether before the law enters into force, or after its entry into force, and approving mandatory prior oversight to monitor compliance with the bylaws of the two chambers of Parliament and the laws? Membership, armistice agreements, and peace treaties, with the constitution, where notification is obligatory is the right of the President of the Republic only. Although presidential decrees in Algeria are outside the scope of judicial oversight as they are immune according to the theory of acts of sovereignty, they are subject to constitutional oversight that belongs to the Constitutional Council in accordance with Article 186 of the Constitution, by expressing its opinion on the constitutionality of the regulations within thirty days from the date of notification. However, At the request of the President of the Republic, this period may be reduced to 10 days in the event of an emergency, in accordance with Article 189, paragraph 01. The organization loses its effect from the day the Constitutional Council decides that this decree is unconstitutional in accordance with the text of Article 191 of the Constitution, after it is notified by the President of the Republic, the Speaker of the National Assembly, the President of the National People’s Assembly, or the Prime Minister. It can also be notified by 50 deputies. Or 30 members of the current constitution, where the Algerian constitutional founder added to strive to distribute the scope of control and protect the rights and freedoms of individuals, which is the introduction of Article 188 of the current constitution that allows both the Supreme Court and the Council of State to notify the Constitutional Council of claiming unconstitutionality when one of the parties claims in the trial The legislative ruling on which the outcome of the conflict depends violates the rights and freedoms guaranteed by the Constitution. Therefore, oversight that grants individuals the right to notify and initiate constitutional oversight, whether through the original lawsuit or through the method of payment, is considered effective oversight that allows affected individuals to challenge the unconstitutionality of a law, protecting their rights and freedoms and away from the political pressures that entitle them to notification and that may It does not interfere in challenging the constitutionality of laws if it serves its own interests. ................ الملخص : آلية الاخطار تشكل محرك الرقابة على دستورية النصوص القانونية ، و إن اختلفت هذه الاخيرة حسب الجهة المصدرة لها ، أو بعبارة أخرى حسب الجهة المخطرة . و رغم تبني المؤسس الدستوري الجزائري ثنائية نظام الاخطار عن طريق إقراره الرقابة الاختيارية على دستورية القوانين ، أين يكون الاخطار بالنسبة للهيئات المخولة حق الاخطار سواء قبل دخول القانون حيز التنفيذ، أو بعد نفاذه ، و إقراره الرقابة الوجوبية المسبقة لمراقبة مطابقة النظام الداخلي لغرفتي البرلمان و القوانين العضوية و اتفاقيات الهدنة و معاهدات السلم ، مع الدستور ، أين يكون الاخطار وجوبيا من حق رئيس الجمهورية فقط . رغم أن المراسيم الرئاسية في الجزائر تخرج عن نطاق الرقابة القضائية باعتبارها محصنة وفقا لنظرية أعمال السيادة ، إلا أنها تخضع للرقابة الدستورية التي تعود للمجلس الدستوري وفقا للمادة 186 من الدستور، من خلال إبداء رأيه في دستورية التنظيمات في ظرف ثلاثون يوما من تاريخ الاخطار ، إلا أنه يجوز و بطلب من رئيس الجمهورية خفض هذه المدة الى 10 أيام في حالة وجود طارئ طبقا للمادة 189 الفقرة 01. و يفقد التنظيم أثره من يوم قرار المجلس الدستوري بعدم دستورية هذا المرسوم وفقا لنص المادة 191 من الدستور، وذلك بعدما يتم إخطاره من رئيس الجمهورية أو رئيس مجلس الامة ، أو رئيس أو المجلس الشعبي الوطني ، أو الوزير الاول ، كما يمكن إخطاره من من 50 نائبا أو 30 عضوا من الدستور الحالي ، أين أضاف المؤسس الدستوري الجزائري للسعي جاهدا لتوزيع نطاق الرقابة وحماية حقوق الافراد و حرياتهم ، و هو استحداث 188 من الدستور الحالي التي تسمح لكل من المحكمة العليا ومجلس الدولة بإخطار المجلس الدستوري بالدفع بعدم الدستورية عندما يدعي احد الاطراف في المحاكمة أن الحكم التشريعي الذي يتوقف عليه مآل النزاع ينتهك الحقوق و الحريات التي يضمنها الدستور . و عليه تعتبر الرقابة التي تمنح للأفراد حق الاخطار و تحريك الرقابة الدستورية سواء عن طريق الدعوى الاصلية أو عن طريق أسلوب الدفع ، فهي رقابة فعالة تسمح للأفراد المتضررين الطعن بعدم دستورية قانون ما ، حماية لحقوقهم وحرياتهم و بعيدا عن الضغوطات السياسية المخولة حق الاخطار و التي قد لا تتدخل في الطعن في دستورية القوانين إن كان ذلك يحقق لها مصلحة ما . .................. Résumé : Le mécanisme de notification constitue le moteur du contrôle de la constitutionnalité des textes juridiques, même si celle-ci diffère selon l'autorité qui les émet, c'est-à-dire selon l'autorité notifiante. Même si le fondateur de la Constitution algérienne a adopté un système de double notification en approuvant le contrôle facultatif de la constitutionnalité des lois, où est la notification aux organes habilités à notifier, que ce soit avant l'entrée en vigueur de la loi, ou après son entrée en vigueur, et en approuvant l'obligation préalable de notification ? contrôle du respect des statuts des deux chambres du Parlement et des lois, de l'adhésion, des accords d'armistice et des traités de paix, à la constitution, où la notification est obligatoire, relève du droit exclusif du Président de la République. Bien que les décrets présidentiels en Algérie échappent au contrôle judiciaire car bénéficiant de l'immunité selon la théorie des actes de souveraineté, ils sont soumis au contrôle constitutionnel qui appartient au Conseil constitutionnel conformément à l'article 186 de la Constitution, en exprimant son avis. sur la constitutionnalité du règlement dans un délai de trente jours à compter de la date de notification. Toutefois, à la demande du Président de la République, ce délai peut être réduit à 10 jours en cas d'urgence, conformément à l'article 189, alinéa 01. . L'organisation perd ses effets à compter du jour où le Conseil constitutionnel décide que ce décret est inconstitutionnel conformément au texte de l'article 191 de la Constitution, après notification par le Président de la République, le Président de l'Assemblée nationale, le Président de l'Assemblée populaire nationale, ou le Premier ministre. Elle peut également être notifiée par 50 députés. Ou 30 membres de la constitution actuelle, où le fondateur de la constitution algérienne a ajouté s'efforcer de répartir le champ de contrôle et de protéger les droits et libertés des individus, qui est l'introduction de l'article 188 de la constitution actuelle qui permet à la Cour suprême et au Conseil d'État de notifier au Conseil constitutionnel l'inconstitutionnalité invoquée lorsqu'une des parties réclame au procès la décision législative dont dépend l'issue du conflit viole les droits et libertés garantis par la Constitution. Par conséquent, un contrôle qui accorde aux individus le droit de notifier et d'initier un contrôle constitutionnel, que ce soit par le biais du procès initial ou par le biais du mode de paiement, est considéré comme un contrôle efficace qui permet aux individus concernés de contester l'inconstitutionnalité d'une loi, protégeant ainsi leurs droits et libertés. des pressions politiques qui leur donnent droit à la notification et qui peuvent le faire. Elle n'intervient pas dans la contestation de la constitutionnalité des lois si cela sert ses propres intérêts.